A Model-Based Approach to Support the Automatic Safety Analysis of Multiple Product Line Products - Oliveira, Andre L. de; Braga, Rosana T.V.; Masiero, Paulo C.; Papadopoulos, Yiannis; Habli, Ibrahim; Kelly, Tim (Anais do Simpósio Brasileiro de Engenharia de Sistemas Computacionais (SBESC); 2014: Anais do IV Simpósio Brasileiro de Engenharia de Sistemas Computacionais, 2014)
Software product lines (SPL) have been successfully used in the development of automotive and avionics critical embedded systems. Hazards and their causes may change according to the selection of variants in a particular SPL product. Thereby, lower-level assets like fault trees and FMEA (Failure Modes and Effects Analysis) cannot be reused because they are dependent upon the selection of product variants. In this paper, model-based safety analysis techniques and SPL variability management tools are used together to reduce the effort of product safety analysis by: reusing SPL hazard analysis, and providing automatic safety analysis for each SPL product. Therefore, we propose a model-based approach to support the generation of safety analysis assets for multiple safety-critical SPL products. The proposed approach is illustrated using the Hephaestus variability management tool and the HiP-HOPS model-based safety analysis tool to generate fault trees and FMEA for the products of an automotive hybrid braking system SPL. Applying the approach reduced the effort to perform product safety analysis.